Development of a Longitudinal Curricular Evaluation Framework for Intra- and Interprofessional Teamwork - Jones, Tobie A.; Stilp, Curt C.; Driessnack, Martha; Austin, Jared P.; Tonning, Kristi; Bearden, David T.; Taylor, Cynthia; Brown, Linda; Carney, Patricicia A. (Journal of Research in Interprofessional Practice and Education, 2021)
Objectives: To describe the development and evaluation of a university-wide competency and evaluation framework for intra- and interprofessional education (IPE) teamwork.Methods: Development of the framework was based on existing literature and specific contexts of the schools within our university. Evaluation and program alignment regarding use of the framework were achieved through qualitative interviews with deans of the Schools of Medicine, Nursing, and Pharmacy, and focused on how they evaluated student progression towards the university-wide teamwork competency. Interview data were analyzed using classical content analysis.Results: Despite efforts to carefully design the framework, interviews revealed that significant variation exists regarding when and how both IPE and team-based care are taught and evaluated across schools. Common barriers to interprofessional education included variations in teamwork practices across disciplines, scheduling challenges, and lack of resources for implementation. Recommendations for how to align teaching and evaluation activities with the framework are posed.Conclusions: Longitudinally tracking the development of interprofessional competencies within/across health professions schools requires careful planning and collaboration among institutional leaders, interprofessional educators, program evaluators, and students. The information gained from this process provides insights toward implementing future high-quality IPE in teamwork and other inter- and intraprofessional competencies, which may be helpful to others.